English English - Muhammad Fuad Hanan; Syamsul Hadi (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2025)
This study aimed to analyze the influence of social media, social interaction, collaboration, and promotion on the continuity of written works and writers' income on the KBM App platform. Using a correlational quantitative method, data was collected through an online survey involving 100 KBM App writers selected using the Slovin sampling technique from a total population of 114,902 writers. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that promotion and collaborative promotion significantly influenced social media usage, ultimately having a positive impact on writers' income. Additionally, social interaction directly affected the continuity of written works, although it did not significantly contribute to increased social media engagement. These findings highlighted the crucial role of digital marketing strategies in improving the financial well-being of writers on digital platforms.